ANALISIS DALAM PROSES PEMBENTUKAN UNDANG-UNDANG CIPTA KERJA PERPSPEKTIF UNDANG-UNDANG NOMOR 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Munawar Munawar; Marzuki Marzuki; Ibnu Affan (LPPM YPITI, 2021)
The process of establishing the Job Creation Law has established a series of principles, both formally and materially. The formation of the Job Creation Law tends to ignore the principles of the formation of laws and regulations, both formal and material principles. The formulation of the problem in this thesis is how the design and ratification of Law Number 11 of 2020 concerning Job Creation is in accordance with Law No. 15/2019 concerning the Establishment of Legislations, what is the position of Law Number 11 of 2020 concerning Job Creation in the perspective of Law No. 15/2019 concerning the Formation of Legislation, how is the impact of the implementation of Law No. 11 of 2020 concerning Job Creation on the prevailing statutory system in Indonesia. The research method used is descriptive analysis that leads to normative juridical legal research, namely research conducted by referring to legal norms, namely researching library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that the process of designing and ratifying Law Number 11 of 2020 concerning Job Creation is not in accordance with Law No. 15/2019 concerning the Formation of Legislations because at the planning and drafting stages it turned out to be Academic Papers and the Basis for Drafting Legislation Programs. National has no legal force. The position of Law No. 11 of 2020 concerning Job Creation in the perspective of Law No. 15/2019 concerning the Formation of Legislation is to have a strong position in the structure and national legal system. The impact of the implementation of Law Number 11 of 2020 concerning Job Creation on the applicable legal system in Indonesia is that the Job Creation Law has procedural defects because in the process the public does not know the standard and official text related to the Job Creation Act, and is not involved directly in the discussion and ratification, which is contrary to the constitutional rights as citizens regulated in the 1945 Constitution of the Republic of Indonesia.